2017
DOI: 10.3390/v9060110
|View full text |Cite
|
Sign up to set email alerts
|

UK Pigs at the Time of Slaughter: Investigation into the Correlation of Infection with PRRSV and HEV

Abstract: Hepatitis E virus (HEV) and porcine reproductive and respiratory syndrome virus (PRRSV) and are both globally prevalent in the pig population. While HEV does not cause clinical disease in pigs, its zoonotic potential has raised concerns in the food safety sector. PRRS has become endemic in the United Kingdom (UK) since its introduction in 1991, and continues to cause considerable economic losses to the swine industry. A better understanding of the current prevalence and diversity of PRRSV and HEV in the UK, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Thus, this may indicate that coinfection regulates the duration of viremia in HEV. However, another study found that there was no significant correlation between PRRSV-positive and HEV-positive status in plasma, tonsil and cecal content samples ( 78 ).…”
Section: Co-infection Of Prrsv and Virusesmentioning
confidence: 99%
“…Thus, this may indicate that coinfection regulates the duration of viremia in HEV. However, another study found that there was no significant correlation between PRRSV-positive and HEV-positive status in plasma, tonsil and cecal content samples ( 78 ).…”
Section: Co-infection Of Prrsv and Virusesmentioning
confidence: 99%